Удосконалення автоматизованої установки вакуумного фракціонування з одержання вузьких фракцій ефірних олій - Чепель, Наталія Василівна; Фролова, Наталія Епінетівна; Усенко, Віталій Олександрович; Науменко, Ксенія Андріївна; Тищенко (Усатюк), Олена Михайлівна (My University, 2013)
Для досягнення одержання запланованих вузьких фракцій ефірних олій, що використовуються в технології натуральних ароматизаторів, було запропоновано удосконалення автоматизованої установки вакуумного фракціонування ефірних олій. Проведено розрахунки основних характеристик, конструкції та розмірів установки вакуумної ректифікації. Оцінку правильності удосконалення установки проводили з застосуванням газової хроматографії, що дала змогу визначити компонентний склад одержаних фракцій на прикладі ефірної олії кропу. The improvement of the automated setting of a vacuum fractionating for narrow fractions of essential oils. For achievement of receipt of the planned narrow fractions of essential oils which are used in technology of natural flavors, the improvement of the automated setting of a vacuum fractionating of essential oils was offered. The calculations of basic descriptions, construction and sizes of setting of a vacuum rectification are conducted, in particular: a number of theoretical piatis of rectification colon must be 10; a type of rectification colon is attachment; a diameter of rectification colon is 5 see, and a height is 80 see. An apparatus improvement consisted in editing another attachment which enables to get the necessary height of rectification column. There was the best satiation of pair by the set component and division on planned narrow fractions of essential oils. Estimation the rightness of improvement of setting was conducted with the use of gas chromatography which enabled to define component composition of the got fractions on the example of the essential oil of the dill.
Keywords: ефірні олії; essential oils; вакуумне фракціонування; vacuum fractionating; вузькі фракції ефірних олій; narrow fractions of essential oils; кафедра експертизи харчових продуктів; кафедра готельно-ресторанної справи; кафедра технології молока і молочних продуктів; кафедра технології оздоровчих продуктів